Economic botany : a comprehensive study - Kochhar, S. L. (New York : Cambridge University Press, 2016)
"Provides vivid information about the history of plant exploration, migration, domestication, distribution and crop improvement"--
Includes bibliographical references and index.
Keywords: Botany, Economic; Plants, Useful; Crop improvement